Pengaruh Marketing Innovativeness dan Market Sensing Capabilities terhadap Marketing Performance UMKM Batik Jawa Tengah - Nurudin Nurudin (Universitas Muhammadiyah Surakarta, 2023)
The main purpose of this study is to determine the effect of the relationship between marketing innovation and market sensing capability on marketing performance. The total population in this study was 1,364 SMEs of Central Java Batik, then the sampling method was purposive sampling technique with a sample of 100 respondents. The data of this research is in the form of quantitative data with data analysis techniques using SPSS tools. The results show that the coefficient of marketing innovation variable is 0.255 with p value = 0.001 0.05 which means marketing innovation has a positive and significant effect on marketing performance and market sensing capability variable obtained a coefficient of 0.336 with p value = 0.000, because p value 0.000 0.05 so market sensing ability has a positive and significant effect on marketing performance